Prevalence of Gambling Disorder Among Prisoners: a Systematic Review - Banks, James (International journal of offender therapy and comparative criminology, 2020)
This article presents the first systematic review of studies on the prevalence of gambling disorder among prisoners across international jurisdictions. Only original studies that were published in English and employed reliable and valid screening tools are included in this analysis. The review finds that rates of problem or pathological gambling in prison populations are highly variable, ranging from 5.9% to 73% of male and female inmates surveyed. Nevertheless, recorded rates of problem and pathological gambling among inmates are consistently and significantly higher than rates of problem and pathological gambling recorded among the general population. The review indicates that the institution of problem gambling treatment programmes in carceral settings is necessary, to aid community re-entry and reduce the likelihood of re-offending. Moreover, it is suggested that the screening of inmates should become standard practice across penal institutions and other criminal justice organisations, with a view to better addressing the needs of offenders.